Cutaneous Ewing's sarcoma of scalp with lung metastases in an elderly female: A rare case report - Nag, Pulkit; Thipparampalli, Joseph; Pareek, Puneet (Clinical cancer investigation journal, 2019)
Ewing's sarcoma (ES) is a primitive neuroectodermal tumor. It is usually a primary bone tumor but rarely occurs in the skin and subcutaneous tissues (primary cutaneous ES [PCES]). It usually involves the deep subcutaneous tissue or muscles and rarely occurs as primary skin cancer. Most patients are white, women, and in the second decade of life. The diagnosis is made by aspiration cytology, histochemical stains, immunohistochemistry, electron microscopy, cytogenetics, and molecular genetics of translocations. Due to their rarity and morphological similarity to other cutaneous tumors, ESs are subject to being clinically and pathologically underdiagnosed. Cutaneous ES has a better prognosis than primary bone or soft-tissue ES, with a survival rate of 91% in 10 years and the presence of metastasis being rare. At present, no specific treatment guidelines inform the management of cutaneous Ewing tumor. The treatment modalities are extrapolated based on the management of bone ES while includes neoadjuvant chemotherapy, surgery, adjuvant chemotherapy (±radiotherapy), and autologous bone marrow transplantation in high-risk patients. Standard first-line treatment for patients with these tumors includes chemotherapy with a five-drug regimen of vincristine, doxorubicin (Adriamycin®), and cyclophosphamide, alternating with ifosfamide and etoposide. We report a rare case in a 60-year-old female diagnosed as PCES with lung metastases, treated by palliative chemotherapy.